Effectiveness Of Water And Air Pumps On The Growth And Production Of Lettuce (Lactusa sativa L.) On Various Kinds Of Media With Hydroponic Systems - Teguh Supriyadi; Endang Suprapti; Tyas Soemarah Kurnia Dewi; Agus Budiyono; Daryanti; Supadi (JURNAL ILMIAH AGRINECA, 2022)
Lettuce (Lactusa sativa L.) is one of the vegetable commodities that can be grown in tropical and subtropical areas. This research was conducted in March-June at the Green House of FP.UTP. This study uses the factorial method with a completely randomized design (CRD), a factorial pattern consisting of two factors. 1) Use of a Pump (P0: Without a Water Pump (Aquarium Pump) and Air Pump (Aerator), P1: Using only a water pump, P2: Using only an air pump, P3: A combination of using a water pump and air pump. 2) use of planting media (S) Rockwool; cocopeat, moss, repeated three times. The results showed 1) Pump use treatment (P) had a very significant effect on the parameters of plant height (cm), stem diameter (cm), number of leaves (strands), leaf width (cm), fresh plant weight (g), dry weight plants (g), consumption weight (g), number of leaves consumed (strands), and root length (cm) on the growth of lettuce (Lactusa sativa L). 2) The treatment using media (S) had a very significant effect on the fresh weight parameters of the roots (g). It significantly affected the root volume parameters (mm) on the growth of lettuce (Lactusa sativa L). 3). The combination of pump and media treatment had a significant effect on the root volume parameter (mm) on the growth of lettuce (Lactusa sativa L). 4). The best result, namely the consumption weight, was achieved in the P3S2 treatment (Combination of treatment using a pump and cocopeat media) with a value of 119.33 g.